Building a Kinetic Expectation Scale for Goalkeepers during a Penalty Shootout of The Premier League Football Clubs for the 2018-2019 Sports Season in The Republic of Iraq - Mutair Hamidi Al-Karizi, Maytham; Abdul Jabbar Murad, Imad; Sameer Dhannoon, Omar (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to build the kinetic prediction scale for soccer Premier League clubs in soccer during a penalty shootout for the 2018-2019 sports season for the Republic of Iraq, and the researcher used the descriptive method of the sample and applied the basic study to a sample. (19) Goalkeeper clubs from the English Football League (Figure Finder) were randomly chosen, and they used appropriate statistical treatments. Six axes (self-confidence, focus attention, kinematic response, emotional balance, skill and challenge, and facing anxiety) were extracted as the main axes of the kinetic expectation scale of soccer goals in the Premier League in football and reached the presence of standard levels dimensions of the scale and we recommend it to measure The kinetic expectation of the goalkeepers.